2010
DOI: 10.26719/2010.16.3.318
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic fatalities in Qatar, Jordan and the UAE: estimates using regression analysis and the relationship with economic growth

Abstract: Smeed's equation is a widely used model for prediction of traffic fatalities but has been found inadequate for use in developing countries. We applied regression analysis to time-series data on vehicles, population and traffic fatalities in the United Arab Emirates (UAE), Jordan and Qatar. The data were fitted to exponential models for fatality prediction, producing an average absolute error of 20.9% for Qatar, 10.9% for Jordan and 5.5% for the UAE. We found a strong linear relationship between gross domestic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In rapidly developing economies, increases in mobility and vehicle penetration often exceed safety-focused improvements in infrastructure, traffic policy enforcement, and norms around road safety (Bener et al, 2010; Kopits & Cropper, 2005; Winston, Rineer, Menon, & Baker, 1999). It is in these contexts that multi-sectoral road safety responses are essential.…”
Section: Introductionmentioning
confidence: 99%
“…In rapidly developing economies, increases in mobility and vehicle penetration often exceed safety-focused improvements in infrastructure, traffic policy enforcement, and norms around road safety (Bener et al, 2010; Kopits & Cropper, 2005; Winston, Rineer, Menon, & Baker, 1999). It is in these contexts that multi-sectoral road safety responses are essential.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of oil, Qatar has experienced a rapid growth in socioeconomic status which resulted in high motorization rate that leads to increased MVCs. [ 12 ] Moreover, economic growth in Qatar has led to the remarkable increase in incidence of MVCs, occupational injuries, as well as assaults and stab injuries resulting in the death and the disability. [ 13 ] In 2001, one report from Qatar showed that in MVCs, the abdominal injury patients constituted 0.45% of total trauma admissions and 12.6% of all admitted cases to the surgical Intensive Care Unit (ICU).…”
Section: Introductionmentioning
confidence: 99%
“…However, some recent time-series studies have not shown the inverted U-shaped Kuznets Curve . Longitudinal studies in Oman (Al-Reesi et al 2013 ) and Qatar (Bener et al 2010 ), both high-income countries in the past three decades, actually found RTFs increased monotonically with economic growth. A cross-sectional exploration (Bhalla and Mohan, in preparation for publication) using recent RTFs data for all countries based on the 2010 Global Burden of Disease Study (Global Road Safety Facility et al 2014 ) and the 2013 WHO Global Status Report on Road Safety (World Health Organization 2013 ) showed no clear relationship between gross national income (GNI) per capita and RTFs but revealed large variations of RTF status for countries of similar GNI per capita.…”
Section: Introductionmentioning
confidence: 99%